Prototype acupressure model as a therapy tool based arduino UNO on blood pressure in hypertension patients grade I - Hidayat, Dita Nafira; taadi, taadi; Santjaka, Aris (Universitas Muhammadiyah Semarang, 2024)
Hypertension is a non-communicable disease which is a serious health problem. The number of hypertension cases in Southeast Sulawesi province in 2018 was 54,127 people (33.62%). In the city of Baubau, the prevalence of hypertension was 3,606 cases in 2018. The research objective is to determine the effectiveness of using the prototype acupressure model as tool therapy based Arduino UNO on blood pressure in hypertensive patients grade I. The research used is Research and Development development prototype acupressure model as tool therapy based Arduino UNO. Test the effectiveness of the model with true eksperiment pretest and posttest with control group design with 30 respondents divided into 2 groups by technique random sampling. Intervention group with prototype acupressure for 4 sessions for 2 weeks duration of 20 minutes continued to consume antihypertensives and the control group received standard treatment of taking antihypertensive drugs. The systolic blood pressure in the intervention group experienced a significant decrease of 13.49%, while that of the control group was 8.48%. The mean of the intervention group after treatment was 150.65 to 130.32 mmHg (p=0.000) while the control group averaged 149.33 to 136.67 mmHg (p=0.001). The diastolic blood pressure decreased by 16.44% while the control group was 5.52%. The mean of the intervention group after treatment was 101.33 to 84.67 mmHg (p=0.000), while the control group averaged 96.67mmHg to 91.33mmHg (p=0,005). Intervention prototype acupressure model as tool therapy based Arduino UNO effective reducing blood pressure in hypertensive patients grade I.